2007
DOI: 10.1007/s11340-007-9097-x
|View full text |Cite
|
Sign up to set email alerts
|

Creep Properties and Recoverability of Double-wall Corrugated Paperboard

Abstract: This paper deals with the characterization of creep properties and recoverability of double-wall corrugated paperboard with A and B flutes at different combined conditions of the ambient temperature 20°C with four kinds of relative humidities and five kinds of constant compression loads. The main feature of this paper is the evaluation on the creep properties and recoverability of double-wall corrugated paperboard with A and B flutes by a series of experimental studies on creep testing apparatus, the analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
(4 reference statements)
0
8
0
1
Order By: Relevance
“…29 Several researchers have investigated the so-called creep deformation of corrugated board and its components under constant load. [30][31][32][33][34][35][36][37][38][39][40][41] The studies concluded that cyclical changes in humidity generally cause higher creep rates than holding humidity constant. Other studies showed that the creep deformation has three stages: primary, secondary and tertiary (see Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…29 Several researchers have investigated the so-called creep deformation of corrugated board and its components under constant load. [30][31][32][33][34][35][36][37][38][39][40][41] The studies concluded that cyclical changes in humidity generally cause higher creep rates than holding humidity constant. Other studies showed that the creep deformation has three stages: primary, secondary and tertiary (see Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Corrugated paperboard as a sandwich structure, being lightweight, high stiffness‐to‐weight ratio, environmentally friendly, and economic advantage, is mainly used to make corrugated box and widely used in transport packaging. A great deal of theoretical and experimental studies has been done to investigate the mechanical properties of corrugated paperboard, such as compressive strength and crush strength, bending defection and flexural stiffness, creasing behaviour, creep property and recoverability, cushioning property, vibration transmissibility, and energy absorption properties . The finite element method simulation was applied to study mechanical behaviours such as stability and collapse of corrugated board panels, elastic behaviour of corrugated paperboard, predictions for the ultimate failure, and buckling and transverse shear .…”
Section: Introductionmentioning
confidence: 99%
“…Angle, channel, and flat are basic form of MLCS, and these components could be modified for various purpose. Various researches for the single-wall (SW) and doublewall (DW) corrugated fiberboard have been performed domestically and internationally (Guo and Zhang, 2008;Park et al, 2011;Sek and Kirkpatrick, 1997). As the public became more aware of environmental problems.…”
Section: Introductionmentioning
confidence: 99%